Patrones de actividad de murciélagos filostómidos en un bosque seco en Honduras - Turcios-Casco, Manfredo A.; Ávila-Palma, Hefer D.; Soler Orellana, José A.; Ordoñez Trejo, Eduardo J.; Ordoñez Mazier, Diego I. (Therya Notes, 2021)
In Honduras, studies about bats are scarce, and it is unknown how the activity of phyllostomid bats is influenced by environmental factors. We describe activity patterns of phyllostomid bat species in Ciudad Universitaria, Francisco Morazán (central Honduras). We did 21 surveys and captured bats with 2 mist-nets from 26 February 2015 to 29 April 2016. Overall, 114 individuals were recorded in 1,428.24 net hours/meter. Based on ANOVA analysis, phyllostomid bats were found between 58 % and 93.5 % of the relative humidity of the air, and between 17.4 ºC and 22.8 ºC of the temperature of the air. Our results indicate interspecific variations in activity of phyllostomid species in the study area. This is the first attempt to describe their activity patterns in a dry forest in Honduras.